Molecular dynamics investigation of the grain boundary migration hysteresis of nanocrystalline Ni under cyclic shear loading. (28th December 2016) - Wang, Peng; Yang, Xinhua; Peng, Di
Abstract: The deformation behavior and grain boundary (GB) response of nanocrystalline Ni under cyclic shear loading are investigated by molecular dynamics simulations. The GB migration hysteresis phenomenon, in which the GB migration displacement lags behind the change in nominal shear strain, is observed in the symmetric tilt GBs for the first time. The elementary structure transformation occurring at the two end segments of the observed GB during GB migration produces a disordered and irreversible state, while the transformation in the middle segment is reversible. Both dislocation retraction and nucleation occur during unloading. Relatively large cyclic strain amplitudes lead to disordered GB segments of greater length, such that the residual GB migration displacement increases with increasing cyclic amplitude. GB migration hysteresis vanishes after the GB becomes immobile owing to a cyclic shear induced transition to a disordered state along its entire length.